Model Negara Kesatuan Republik Indonesia Di Era Reformasi - Mahmuzar, Mahmuzar (Jurnal Hukum & Pembangunan, 2023)
Article 1 Paragraph (1) of the 1945 Constitution stated that the state of Indonesia shall be a unitary state, with the form of a Republic and in article 37 paragraph (5) is affirmed that the form of the unitary state of the Republic of Indonesia may not be amended. There are two kinds of unitary state, namely unitary state with centralistic system and unitary state with decentralized system. The unitary state with decentralized system has five variants, namely; (1) unitary state with centralized decentralized system; (2) unitary state with decentralized system that decentralistic; (3), unitary state with proportional decentralized system; (4) unitary state with federalistic decentralized system, and (5) unitary state with confederate decentralized system. Out of the five unitary state models with the decentralized system, Unitary State of the Republic of Indonesia in this reform era is unitary state with federalistic decentralized system when the the enactment of Law No. 22 of 1999 and Law No. 32 of 2004, and unitary state with centralized decentralization system when the implemented of Law No. 23 of 2014 concerning Local Government.